MODERN COATING TECHNOLOGIES FOR DRUG ELUTING CORONARY STENTS (REVIEW) - E. Y. Zagorulko; A. A. Teslev; E. V. Flisyuk (Разработка и регистрация лекарственных средств, 2019)
The review is devoted to modern polymer coating technologies for drug-eluting coronary stents. The most promising technologies and also the methods which are the subject of experimental investigation have been described. Key advantages and disadvantages of the dip, spray, layer-by-layer, ink-jet, and plasma coating, electrostatic coating and electrochemical deposition methods have been shown. The examples of clinically proven coronary stents have been given. The review illustrates the current level of polymer coating technologies for stents, and also their further development trends.